Evaluasi Atas Pengakuan Pendapatan dan Beban Dalam Kaitannya dengan PSAK No. 36 Tentang Akuntansi Asuransi Jiwa : Studi Kasus Pada PT. Asuransi Jiwasraya (Persero) - Damandari, Sapto Amal (Jurnal Ilmiah Ranggagading (JIR), 2004)
Life insurance has different characteristics compared with other corporation viewed from organizational structure, management style, and its goal. That is why, Indonesia Accountantsâ Association has fixed special standard for insurance, that is Declaration of Finance Accounting Standard No. 36 concerning Life Insurance Accounting. Income is inflow or asset raising from an entity during a certain period derived from delivery or production of goods, services, and other as core business of the firm. The main source of income of PT Asuransi Jiwasraya (Jiwasraya Insurance, Inc.) is premium income and investment yield. PT Asuransi Jiwasraya has applied PSAK (Declaration of Finance Accounting Standard) No. 36 as a guideline in accounting practice of life insurance as an acknowledgement of income and burden in arranging finance account, specifically profit-loss account. Keywords : income acknowledgement; Insurance Accounting